Risk, resilience and retention - a multi-pronged student development model. - Du Plessis, Megan; Benecke, Rene (The IIE, 2014)
The notion of resilience amongst first year students in higher education is of increasing interest as the number of at-risk students is growing and educators are seeking ways of strengthening the whole teaching and learning package. This study investigated a group of 51 first year Public Relations and Communication students at the University of Johannesburg who were identified by the faculty as at-risk students and who had been given provisional passes into the second semester of study. The study was conducted through the use of a questionnaire which related to several internal risk factors but more specifically to the students’ use of the support services offered by the university. These support services are considered by the university to be strategic interventions which, if utilised by the students, may assist in realising their academic success. The study concluded that it is the responsibility of those who structure the learning environment to nurture students specifically through ensuring that the services offered by the university are well utilised by them and thus promote the vision of the university to widen access and improve retention and throughput.
Keywords: First year students; Public relations; at-risk students; Student intervention; Student support; Student retention; Academic success